An analytical approach to entropy production in MHD mixed convection micropolar fluid flow over an inclined porous stretching sheet - Sadighi, Sina; Afshar, Hossein; Jabbari, Mohsen; Ahmadi Danesh Ashtiani, Hossein (Frontiers in Mechanical Engineering, 2022)
This analytical analysis examines the MHD micropolar fluid flow and mixed convection features using entropy production analysis of an inclined porous stretching sheet. Flow field and heat transfer analysis are presented to consider thermal radiation, heat source/sink, Lorentz, and buoyancy forces. The PDEs system is transformed by appropriate similarity variables and turned into a system of high non-linearity coupling ODEs and then solved with the help of an analytical approach. An analytical approach can provide exact explicit solutions for the flow field, heat transport, entropy production, the local skin friction coefficient, the local couple stress coefficient, and the local Nusselt number. It is shown that the magnetic field, mixed convection, and sheet inclination effects can be incorporated together into a single parameter, which is called the magneto-buoyancy-inclination parameter here. In other words, this parameter controls the boundary layer flow. In addition, an experimental procedure called Box-Behnken design (BBD) was employed to analyze the influence of material (K), radiation (Rd), and buoyancy () parameters on entropy production in MHD micropolar fluid flow over the sheet. In order to estimate accurately the optimum entropy generation containing K, Rd, and , we used a quadratic regression model. Based on the results of this investigation, the value of the entropy generation number became larger by decreasing the magneto-buoyancy-inclination parameter. Further, the magnitude of the local couple stress coefficient is decreased as the heat source parameter increases. Keywords: Exact solution; MHD free convection flow; Micropolar fluid; Stretching sheet; Entropy analysis; Response surface methodology.